2020
DOI: 10.1002/ardp.202000025
|View full text |Cite
|
Sign up to set email alerts
|

Coumarin derivatives with anticancer activities: An update

Abstract: Cancer can invade or spread to almost all parts of the body. The increasing morbidity and high mortality of cancer create a great demand for the development of novel anticancer drugs. Coumarin derivatives are ubiquitous in nature and can readily interact with diverse enzymes and receptors in cancer cells via weak bond interactions; hence, coumarin is a highly privileged pharmacophore for the development of novel anticancer agents. This review will focus on the recent development of coumarin hybrids as potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
54
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 93 publications
2
54
0
Order By: Relevance
“…Among those nucleos that have shown promising results, we can point to the bicalutamide, isoxazolones, pyrrole carboxamides, pyridines and N ‐arylpiperazine derivatives, indeno[1,2‐ d ]pyrimidine‐5‐one, imide‐based analogs, hydantoin, benzochromene, benzoquinoline, quinoline, coumarin derivatives, and organometallic‐containing derivatives. [ 9‐14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Among those nucleos that have shown promising results, we can point to the bicalutamide, isoxazolones, pyrrole carboxamides, pyridines and N ‐arylpiperazine derivatives, indeno[1,2‐ d ]pyrimidine‐5‐one, imide‐based analogs, hydantoin, benzochromene, benzoquinoline, quinoline, coumarin derivatives, and organometallic‐containing derivatives. [ 9‐14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Our results showed that coumarin-triazole compounds 3c, d, e, and f significantly inhibited the proliferation of A549cells. Previous studies showed that coumarin-derivated compounds could cause cytotoxicity on various human cancer cell lines [4,13]. Yu et al, [14] showed that coumarin compounds bearing triazole moiety exhibited an important cytotoxic activity against human breast (MDA-MB-231), colorectal (HT-29 and HCT-116), and lung A549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Heterocyclic complexes derived from natural compounds can interact more easily with biological targets due to relatively weak binding in their structure compared to the native form [3]. More than half of the approved drugs are derived from synthetic forms of natural compounds [4]. Coumarin is an important secondary metabolite related to defense mechanisms in the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the insertion of a biologically active morpholine fragment into TSC backbones improved their aqueous solubility and anticancer activity in various cancer cell lines [23,26]. Herein, a biologically active coumarin (or 2H-chromen-2-one) fragment (Chart 1, right) was selected to be incorporated, due to its well-documented wide spectrum of activities, including antibacterial, antifungal, neuroprotective, antiamoebic, anti-inflammatory, and cytotoxic properties [27][28][29][30][31][32][33][34][35][36][37][38]. In addition, another biologically active piperazine fragment was included, since heteroaromatic ring systems are considered highly impactful design elements for the optimisation of key pharmacological parameters [23,39].…”
Section: Introductionmentioning
confidence: 99%